Decreases in markers of monocyte/macrophage activation after hepatitis C eradication in HIV/hepatitis C virus coinfected women. (15th July 2021) - French, Audrey L.; Grennan, Dara; Daubert, Elizabeth; Seaberg, Eric C.; Peters, Marion; Augenbraun, Michael; Fischl, Margaret; Kassaye, Seble; Franco, Ricardo; Kuniholm, Mark; Adimora, Adaora A.; Workowski, Kimberly; et al.
Abstract : Objective: Eradication of hepatitis C virus (HCV) in HIV disease decreases liver and non-liver-related morbidity and mortality. Elevated markers of monocyte/macrophage activation (soluble CD163 and sCD14) are associated with excess non-AIDS morbidity and mortality in HIV. We examined the effect of HCV eradication on these markers in relation to change in hepatic fibrosis. Design: A nested substudy within a longitudinal observational cohort Methods: We studied 126 HIV/HCV-coinfected women successfully treated for HCV, with undetectable HCV RNA at least 12 weeks after therapy completion. sCD163 and sCD14 were measured in serum collected before and after HCV eradication. Results were correlated with changes in markers of hepatic fibrosis. Results: Mean age of participants was 56.3 years, mean CD4 + cell count was 615, and 72% had suppressed HIV RNA. After treatment, sCD163 and sCD14 levels significantly decreased from pre-treatment levels in unadjusted analyses. After adjusting for age, race, hepatic fibrosis status, baseline HCV RNA, CD4 count and HIV RNA status, cigarette smoking, and alcohol use, the decreases in sCD163 and sCD14 remained significant. Decrease in pre-treatment to post-treatment sCD163 were significantly positively correlated with changes in FIB-4 ( r  = 0.250, P  = 0.005) and APRI ( r  = 0.262, P  = 0.003); similarly decrease in sCD14 was significantly positively correlated with changes in FIB-4 ( r  = 0.333, P  = 0.0001) and APRI ( r  = 0.457, P  < 0.0001). Conclusion: HCV eradication is associated with significant reductions in monocyte/macrophage activation markers that correlate with reductions in markers of hepatic fibrosis. These findings support broad access to and early initiation of HCV treatment in order to decrease immune activation and improve health in HIV-infected persons.